Contributions to the orchid flora of Kalimantan II: A new Bulbophyllum sect. Macrocaulia from Mount Bukit Raya, Indonesia - Yudistira, Yuda R.; Randi, Agusti; Joharudin, Didin; Mustaqim, Wendy A. (Phytotaxa, 2025)
A new species of Bulbophyllum section Macrocaulia named Bulbophyllum bukitrayaense Yudistira & Mustaqim is described from the mid-montane forest zone of Mount Bukit Raya, Kalimantan Barat Province. It is similar to Bulbophyllum scabrum but differs in having the lower surface of the labellum with two times approaching margin undulation. The new species also have coarsely rugose upper ¼ surface of the labellum (vs smooth) and ovary covered by papillose-muriculate indumentum (vs glabrous). A full description, notes, and fresh photograph plates are given.